Heavy metal and phenol adsorptive properties of biochars from pyrolyzed switchgrass and woody biomass in correlation with surface properties - Han, Yanxue; Boateng, Akwasi A.; Qi, Phoebe X.; Lima, Isabel M.; Chang, Jianmin (Journal of environmental management, 2013)
In this work, the surface structures of biochars, derived from three types of biomass, switchgrass (SG), hardwood (HW) and softwood (SW) through either fast pyrolysis (FP) in a fluidized-bed reactor (at 500 °C) or slow pyrolysis (at 500° and 700 °C), were studied in detail, and compared with that of the activated carbons obtained by steam activation of the slow pyrolyzed biochars (at 500 °C). The surface acidic functional groups were determined quantitatively by the Boehm Titration method. The adsorptive properties of heavy metals, Zn2+ and Cu2+ onto the biochars and the activated carbons were investigated by the adsorption isotherms and SEM images, and correlated with the surface properties. ATR-FTIR and GC techniques were used to analyze the adsorptive behavior of phenol onto the biochars and activated carbons, and the results demonstrated that phenol adsorption capability is directly proportional to the micropore surface area as well as the combined level of the accessible carboxylic and lactonic groups. The relative adsorption capacity with respect to the biomass precursor follows the order: SW > HW > SG. ► pH 4.8 produced more favorable immobilization conditions for heavy metal. ► Phenol adsorbed onto fast pyrolysis biochar assumed a fast and irreversible process. ► Phenol adsorbed onto slow pyrolysis biochar was eliminated by heating and storage. ► Steam activation assumed a fast adsorption and desorption process for phenol.